Rancang Bangun Sistem Penjatuhan Bibit Singkong (Manihot esculenta Crantz) untuk Meningkatkan Efisiensi Penanaman - Raihan Ramadhan; Warji Warji; Siti Suharyatun; Tamrin Tamrin (Jurnal Agricultural Biosystem Engineering, 2026)
This study aims to design and evaluate the performance of a simple and efficient semi-automatic cassava seed dropping system tailored to farmers’ needs. The system was constructed using mechanical components including a drive wheel, a pulley and belt transmission, and a cylindrical metering device with two dropping chambers synchronized with the rotation of the wheel. Performance tests were conducted to assess planting distance accuracy, seed orientation upon release, operational speed, field capacity, and field efficiency. The results indicate that the system operated as designed, producing an average planting distance of 80.79 cm, closely matching the intended specification. Seed orientation tests showed that 92% of the cuttings fell within an angle of 0°–15°, with an average inclination of 3.8°, aligning with agronomic recommendations for optimal shoot and root development. The tool achieved an operational speed of 0.184 m/s (0.66 km/h), with a theoretical field capacity of 0.01657 ha/h and an actual field capacity of 0.00929 ha/h, resulting in an average field efficiency of 56.10%. These findings demonstrate that the developed semi-automatic seed dropping system can enhance planting efficiency compared with manual methods while producing more uniform planting distance and orientation.